Constructs of shariah audit effectiveness in Islamic financial institutions - Zakaria, Nurazalia; Mohd. Ariffin, Noraini; Zainal Abidin, Norhafizah (2015)
Shariah compliance is utmost importance for the sustainability of Islamic Financial Institutions (IFIs) in the industry as stakeholders will only invest and deal with IFIs that operate within Shariah precepts. As such, Shariah audit is required by Bank Negara Malaysia to provide assurance that IFIs indeed do operate on the basis of Shariah principles. Therefore, this conceptual paper proposes the constructs of Shariah audit effectiveness (SAE) in IFIs. This paper reviews and synthesizes prior literature on internal audit effectiveness and Shariah audit in developing the construct of SAE. The construct consists of criteria of SAE as well as its possible determinants. The determinants comprises of top management support, organizational independence and objectivity, and internal Shariah audit process and activities. The development of appropriate measures for SAE is crucial to assist IFIs in monitoring and assessing how well resources are being utilized in the performance of Shariah audit. Effective Shariah audit practice is expected to provide value-added service to ensure IFIs are operating within the limits of Shariah as well as generating halal profits from its financing and investment activities.